Influence of the Extension and Tax Service to Complience of Personal Tax in Indonesia (Study through Taxpayers in the Tax Court – Jakarta) - Iswanto, Yasir; Sumaryadi, I Nyoman; Achmad, Mansyur; Ruhana, Faria (Budapest International Research and Critics University, 2022)
This research will be limited/limited regarding specific matters relating to government policies (efforts) in increasing compliance, socializing and growing awareness of taxation, to people who are at least approaching